Bagaimanakah Dampak Analisis Kebutuhan Dasar Siswa Terhadap Hasil Belajar Siswa di SMA Islam NU Pujon pada Mata Pelajaran Kimia? - Munfarikha, Ninik; Zuhria, Viki Arina; Islam, Rukmana Fachrul; Weri, Firda; Sahar, Adnan; Obina, Wilfrida Mayasti (Indo-MathEdu Intellectuals Journal, 2024)
A safe and comfortable school is a school that is able to foster students' intrinsic motivation through a positive culture, namely by meeting the basic needs of students as the basis for determining an appropriate learning model to get learning outcomes that meet the KKM. This study aims to determine the impact of the analysis of students' basic needs on the achievement of learning outcomes, especially in chemistry subjects at SMA Islam NU Pujon. The sample of the basic needs analysis research is 398 students of NU Pujon Islamic High School for the 2024/2025 school year and the research sample for student learning outcomes for chemistry subjects is classes XI-4 and XII-2 with a mixed method explanatory design research method. The results of the study were obtained that the results of the analysis of the basic needs of NU Pujon Islamic High School students for the 2024/2025 school year with the need for pleasure 25.7%, the need for affection and acceptance 25.4%, the need for freedom 23.5%, and the need for power 25.4%. The average student learning outcomes for chemistry subjects were obtained in class Xl-4 of 77.9 and XII-2 of 79.22. The findings showed that the learning outcomes of students for Chemistry in the two classes were above the school KKM